Institutional Optimization Paths for Government Regulation of Platform Capital Irregularities in Live Streaming Economy - Yin Chengyuan; Song Shuhua; Linghu Yin (International Journal of Educational Research & Social Sciences, 2026)
With the rapid expansion of live streaming economy, platform capital has penetrated all links of industrial operation. Driven by profit motives, many platform enterprises produce irregular capital behaviors such as predatory investment, exclusive traffic agreements, vicious subsidy competition and data-driven market monopoly, which bring severe challenges to traditional government regulatory framework. Based on regulatory economics theory and platform governance theory, this paper sorts out the typical conflicts between existing regulatory systems and platform capital operation characteristics, analyzes institutional obstacles including regulatory fragmentation, lagging digital rules, inadequate cross-department coordination and weak accountability mechanism. This research focuses on institutional innovation of government supervision, and puts forward targeted optimization paths from perfecting special regulatory laws, building whole-chain capital monitoring system, realizing coordinated multi-department supervision, improving algorithm transparency mechanism and constructing long-term regulatory credit system. The conclusions can provide policy reference for standardizing platform capital and promoting standardized development of live streaming business ecosystem.